2015
DOI: 10.1016/j.gpb.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Y-Chromosome Short Tandem Repeat Variants Detected through the use of Massively Parallel Sequencing

Abstract: Massively parallel sequencing (MPS) technology is capable of determining the sizes of short tandem repeat (STR) alleles as well as their individual nucleotide sequences. Thus, single nucleotide polymorphisms (SNPs) within the repeat regions of STRs and variations in the pattern of repeat units in a given repeat motif can be used to differentiate alleles of the same length. In this study, MPS was used to sequence 28 forensically-relevant Y-chromosome STRs in a set of 41 DNA samples from the 3 major U.S. populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…In some mixtures, CE data indicate a single source sample or a two-person mixture, where NGS detects alleles from three and upwards of five or more DNA contributors (David Ballard, personal communication). Since NGS detects and identifies intra-STR sequence variants [88][89][90], the total complement of alleles are provided, at the nucleotide level. Mixture studies described here demonstrated the ability of the MiSeq FGx TM System to detect shared, and unshared (unique, obligate) minor contributor alleles at less than 5% of the major donor.…”
Section: Discussionmentioning
confidence: 99%
“…In some mixtures, CE data indicate a single source sample or a two-person mixture, where NGS detects alleles from three and upwards of five or more DNA contributors (David Ballard, personal communication). Since NGS detects and identifies intra-STR sequence variants [88][89][90], the total complement of alleles are provided, at the nucleotide level. Mixture studies described here demonstrated the ability of the MiSeq FGx TM System to detect shared, and unshared (unique, obligate) minor contributor alleles at less than 5% of the major donor.…”
Section: Discussionmentioning
confidence: 99%
“…While there are many reasons for this, a primary factor has been the lack of developmentally validated and commercially available start-to-finish kits targeting the marker systems (such as short tandem repeats; STRs) routinely typed for forensic purposes. Several papers in recent years have demonstrated the utility and potential of STR sequencing by NGS methods, however these studies have typically employed custom assays developed in-house ( [2][3][4][5][6][7][8][9][10], for example). An additional barrier to the implementation of STR sequencing had been the absence of software programs specifically intended for STR sequence data assembly, alignment and representation, though this gap has been directly addressed in the past few years by open-source solutions developed with forensic use in mind [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, the research community has shifted work to Miseq (7,11,12,14,16,(23)(24)(25)(26)(27) and Ion Torrent NGS machines (9,10,13,15,28) because 454 sequencers are no longer supported by their producer. Typing results for 48 autosomal STR markers (11,12,22,24), 29 Y-STR markers (10,24,25), and 9 X-STR markers (24) have been reported. For data analysis, software such as STRait Razor (29,30), MyFLq (31,32), STRinNGS (33) has been developed.…”
mentioning
confidence: 99%
“…Sample types including commercial genomic DNA (12,24), blood (4,7,8,10,23), saliva (5,17,23,28), buccal swabs (4,8,24), semen (9,24,28), vaginal secretions (28), skin (28), bone (9,23), and muscle (9) have been successfully genotyped with NGS. Population data for African American, Caucasian, Hispanic (11,25,27), Danish (6), and East Asian (10,27) are documented.…”
mentioning
confidence: 99%